Letter (copy) : Basque Children - Tewson, Vincent
1938-01-06 038-0173-001 HVT/FC/EK/395. Secretary's. 6th January, 1938. Mr. H. Cobb, The Salvation Army, Penge and Beckenham Corps, 9, Kingswood Road, Penge, London, S.E.20. Dear Mr. Cobb, BASQUE CHILDREN. Very many thanks for your letter of the 4th instant inviting me to attend your gathering on January 26th. Unfortunately I have to leave for the Midlands in the early evening and consequently I shall be deprived of the pleasure which it would have given me to accept your invitation. Yours sincerely, 292/946/38/173(I)